Significados sobre el ser migrante, en el caso de la parroquia de Pinllo del cantón Ambato. - Yánez Agualongo, José Luis (2020)
This research addressed the problem of migration and its impact on the daily life of the Ecuadorian population, with the aim of identifying the meaning of being a migrant in the Venezuelan community after the events that have been generated in the population of the Pinllo parish of Tungurahua Province For which a methodology of bibliographic and field design was used, with a mixed qualitative and quantitative approach, applying the survey and discussion group techniques to determine the perceptions of both Venezuelan migrants and managers of Pinllo neighborhoods, about the reality of migrants and the impact that this situation has generated in the community. The results obtained from the research have made it possible to show that in the population, mainly negative perceptions have been generated, characterized by social prejudices about Venezuelan migrants, because they have not been able to have a direct interaction that allows them to share ideas, experiences, dreams, desires and recognize themselves as equals, so it is necessary to foster empathy, tolerance and respect.